Determination of Solid State Solubility of the Components in the Ag-Ge Film System - A.A. Minenkov; S.I. Bogatyrenko; A.P. Kryshtal (Журнал нано- та електронної фізики)
The efficiency of determination of solid state solubility of the components in the system with an eutectic type of interaction (Ag-Ge) by means of measuring the sample electrical resistance during thermal cycling has been shown. Film systems were formed in a vacuum by sequential condensation of components. The solubility curve of germanium in silver, obtained from the study of the samples with silver film thickness of 100 nm, is in good agreement with available literature data. The activation energy of grain-boundary diffusion has been estimated as 0,8 eV.